Kearifan Lokal Sebagai Modal Sosial Dalam Mewujudkan Pariwisata Berkelanjutan: Studi Fenomenologis Terhadap Masyarakat Pesisir - Shanty Ratna Damayanti; Sri Utami Ady (CAPITAL: Jurnal Ekonomi dan Manajemen, 2026)
Abstract This study aims to explore the role of local wisdom as social capital in realizing sustainable tourism through a phenomenological study of coastal communities. The research addresses the challenge of balancing economic growth in tourism development with the preservation of cultural identity and environmental sustainability, focusing on the Larung Sesaji tradition at Pantai Papuma. Using a qualitative phenomenological approach, data was collected through in-depth interviews with key informants including local cultural leaders, fishermen, tourism officials, and community members. The analysis highlights that Larung Sesaji functions not only as a ritual for cultural preservation but also as an educational medium that strengthens community identity, transmits ecological knowledge, and promotes social solidarity. This tradition supports sustainable tourism by maintaining the continuity of local wisdom amid modernization, enhancing community resilience, and fostering economic opportunities through cultural tourism. The study concludes that integrating local cultural practices with tourism development effectively balances tradition and economic progress while empowering coastal communities. Keywords: Local wisdom, Larung Sesaji, sustainable tourism, Pantai Papuma